Integrating cotyledon-based virus-induced gene silencing with visual marker promises a rapid, highly effective validation of gene functions in Nepeta cataria - Yu, Zongxia; Lv, Ruo; Hong, Bo; Yang, Lei (Frontiers in Plant Science, 2025)
Nepeta spp. generate volatile nepetalactone iridoids that have cat-attractant and insect-repellent activities. They differ from typical mint family (Lamiaceae) iridoids, which are non-volatile glucosides, and also vary from other species in the Nepetoideae sub-family, which do not generate iridoids. The chemistry and evolution of Nepeta make it suitable for further investigation. However, the lack of transgenic technology hampers the molecular and genetic investigations in Nepeta. Virus-induced gene silencing (VIGS) is a powerful tool to detect gene functions in vivo. Here, we constructed a modified VIGS method in Nepeta cataria, using cotyledon infiltration, with the gene silencing effect spreading to the first two pairs of true leaves. The VIGS efficiency reached as high as 84.4%, and the procedure takes only 3 weeks. We employed this method to validate the role of geraniol 8-hydroxylase in nepetalactone biosynthesis with ChlH as a visual marker in N. cataria. The method is also applicable to Nepeta mussinii. Thus, we developed an easy and effective VIGS approach, which will be advantageous for endogenous gene studies in two Nepeta species and holds the potential for application in other plants.